Building a National Open Access Repository: The MAREN Experience - Kumwenda, Jones (My University, 2026)
This presentation was made as part of the AfricArXiv Open Science Webinar Series. It discusses on MARENs journey in building the Malawi national repository. Specifically the presentation focuses on the following: Practical roadmap for building a national repository Importance of multi-stakeholder collaboration Key technical and governance considerations Real-world lessons: what works and what doesn’t Strategies for driving adoption and engagement
Keywords: MAREN; National Repository; Open Science; Malawi